Regla de Osha-Ifá ou Santería: práticas religiosas, transformações e desigualdades sociais no contexto da atualização do modelo econômico e social cubano - Braffo Conde, Naile (2022)
The economic, political and social transformations implemented in Cuba since 2009 have had consequences in different spheres of society: both in the reconfiguration of the Cuban social structure and with it, in different dimensions of equity; as well as in changes in the development of cultural processes, in the subjectivity, perceptions and aspirations of people, which exerts influence on the symbolic-social imaginary, such as religious practices. Thus, the thesis proposed as an object of study the production of social inequalities between practitioners of the Osha-Ifá Rule or Santeria -a Cuban religion of African origin- in the context of these transformations. There are few studies that study the social inequality-religion relationship in Cuban society, therefore, in order to contribute to the visibility of a problem that reveals these absences and try to cover gaps, the present proposal has as a general objective to explain the relationship between the development of religious practices within the Osha-Ifá Rule or Santería system in Havana and the (re)production of patterns of social inequality among practitioners, according to the use of the structure of opportunities, in the context of these transformations. The methodological strategy moved on two levels: on the one hand, an empirical level, based on the direct interpellation of the social actors; while, on the other, a theoretical sense was given to the information generated during the investigative process, as well as the analysis of the relationship of the development of religious practices, structuring of networks of relationships and processes of inequality in the framework of the transformations implemented. (AU)